MANFAAT TEKNOLOGI DALAM PENDIDIDKAN AGAMA ISLAM - Unik Hanifah Salsabila; Prima Laillatul Ramadhan; Naufal Hidayatullah; Syifa Nur Anggraini (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2022)
Islamic Religious Education is a subject which in Indonesia has been given from an early age to students. The reason for giving Islamic Religious Education subjects is to introduce Islamic teachings and instill positive values ​​for students in accordance with the guidance of the Qur'an and Al-Hadith. Educators have a noble goal in delivering Islamic Religious Education subjects, namely educators not only want to share knowledge about the world, but educators also want to share knowledge of the world and provide provisions for the hereafter to their students. However, as time goes by, educators are required to always keep up with the times, which aims to make improvements and improve the quality of education itself. So that in implementing this strategy, educators are expected to be able to understand and apply existing technological developments in learning activities. This is because in this era of modernization, the role of technology is very much needed because with technology we are able to carry out various activities more easily, especially in terms of education.